Salmonella Gallinarum delivering M2eCD40L in protein and DNA formats acts as a bivalent vaccine against fowl typhoid and H9N2 infection in chickens - Irshad Ahmed Hajam; Jehyoung Kim; John Hwa Lee (Veterinary Research, 2018)
Abstract Fowl typhoid (FT), a septicemic disease caused by Salmonella Gallinarum (SG), and H9N2 influenza infection are two economically important diseases that affect poultry industry worldwide. Herein, we exploited a live attenuated SG mutant (JOL967) to deliver highly conserved extracellular domains of H9N2 M2 (M2e) to induce protective immunity against both H9N2 infection and FT. To increase the immunogenicity of M2e, we physically linked it with CD40L and cloned the fusion gene into either prokaryotic constitutive expression vector pJHL65 or mammalian expression vector pcDNA3.1+. Then pJHL65-M2eCD40L or pcDNA-M2eCD40L recombinant plasmid was electroporated into JOL967 strain and the resultant clones were designated as JOL2074 and JOL2076, respectively. We demonstrated that the chickens vaccinated once orally with a co-mix of JOL2074 and JOL2076 strains elicited significantly (p < 0.05) higher M2e-specific humoral and cell-mediated immunity compared to JOL2074 alone vaccinated group. However, SG-specific immune responses were comparable in both the vaccination groups. On challenge with the virulent H9N2 virus (105 TCID50) at 28th day post-vaccination, chickens that received a co-mix of JOL2074 plus JOL2076 strains exhibited significantly (p < 0.05) lower lung inflammation and viral load in both lungs and cloacal samples than JOL2074 alone vaccinated group. Against challenge with the lethal wild-type SG, both the vaccination groups exhibited only 12.5% mortality compared to 75% mortality observed in the control group. In conclusion, we show that SG delivering M2eCD40L can act as a bivalent vaccine against FT and H9N2 infection and further studies are warranted to develop this SG-M2eCD40L vaccine as a broadly protective vaccine against avian influenza virus subtypes.